Assay of Lercanidipine Hydrochloride with Azocaramine-G, Fe(III)/K3[Fe(CN)6] and Folin Ciocalteu Reagent - Manikya Sastry, T.; Ram Kumar, G. (Asian Journal of Chemistry, 2010)
Three simple and sensitive visible spectrophotometic methods (A-C) have been developed for the assay of lercanidipine hydrochloride in bulk and formulations. Method A is based on the formation of ion-association complex with azocaramine-G (ACG) which was extracted into chloroform (lmax = 540 nm). Method B is based on the formation of coloured complex with K3[Fe(CN)6] in presence of Fe(III) (lmax = 730 nm). Method C is based on the oxidation of drug with Folin-Ciocalteu reagent (lmax = 750 nm). The results of analysis have been validated statistically. Recoveries range from 99.4-100.5 % for the routine assay of lercanidipine hydrochloride formulations.